Vertical Orientation Probability Matters for Enhancing Nanoparticle‐Macrophage Interaction and Efficient Phagocytosis. Issue 5 (8th March 2022) - Hu, Wenli; Gu, Zhengying; Zhao, Liang; Zhang, Ye; Yu, Chengzhong
Abstract: The geometry of nanoparticles has a profound effect on their interactions with macrophages. For an elongated geometry, the well‐known curvature‐dependent phagocytosis mechanism is still under debate, presumably because another important parameter, the probability of orientation, is overlooked. To verify this hypothesis, it is demonstrated that increasing the probability of the preferred vertical orientation is an efficient strategy to significantly enhance macrophage phagocytosis and uptake. This is achieved via a well‐designed hexapod nanoparticle in comparison with a monopod counterpart. The hexapod nanoparticle can achieve ≈100% close‐to‐vertical orientation, thereby favoring phagocytosis. This discovery provides a new insight into the design of nanomaterials for macrophage‐oriented bioapplications. Abstract : Increasing the probability of vertical orientation of nanoparticles is an effective strategy to enhance their interactions with macrophages. This is achieved via a well‐designed hexapod nanoparticle in comparison with a monopod counterpart. The hexapod nanoparticle can achieve ≈100% close‐to‐vertical orientation, thereby favoring phagocytosis. This discovery provides a new insight into the design of nanomaterials for macrophage‐oriented bioapplications.